Implementing precision agriculture in the oil palm industry: a case of oil palm management system (OPAMS) - Sam, Thoong Hai (2018)
Sustainable agriculture slowly replaces the conventional agriculture practice as due to the need of having sustainable agriculture management to address mainly food scarcity issue over the world; and at a micro-level it’s advancement of technological means in order to adapt to the macro environment changes. The need of drastic changes in the global food system in order to achieve a more sustainable agriculture is inevitable. Agriculture industry stakeholders, especially those in oil palm industry, reckon the significance of pursuing sustainability due the competitiveness in the industry. Moreover, rigorous requirements which imposed by sustainable organizations and authorities has given rise to the industry stakeholders for continually seeking for better solutions to minimize the total operating cost. Yet even though these scenarios are what satisfies and act as the market drive to promote the research in precision technologies, the practices of precision technologies in Malaysia’s oil palm industries still lack in its pace. This research aims to develop a sustainable precision agriculture management system for the oil palm industry. Through semi-structured interview session, industry stakeholders revealed their perceptions on precision agriculture technologies. They also shared their experiences and obstacles they encountered during the implementation of precision agriculture technologies in their organization. The research then moved forward to the development of Oil Palm Management System (OPAMS) which serves as a monitoring and data management system to justify the decision making in oil palm plantation operational process to achieve sustainable goal. The system assists them in monitoring, control and properly manages their resources, including fertilizers, chemical, pesticides, energy and water with better efficiency. The research raised the awareness of precision agriculture practices in oil palm industry, allow industry stakeholders taking sustainability into account while making operating investment and management decisions.